IL-17 mediates articular hypernociception in antigen-induced arthritis in mice - Pinto, Larissa G; Cunha, Thiago M; Vieira, Silvio M; Lemos, Henrique P; Verri, Jr, Waldiceu A; Cunha, Fernando Q; Ferreira, Sergio H (Pain (Amsterdam), 2010)
IL-17 is an important cytokine in the physiopathology of rheumatoid arthritis (RA). However, its participation in the genesis of nociception during RA remains undetermined. In this study, we evaluated the role of IL-17 in the genesis of articular nociception in a model of antigen (mBSA)-induced arthritis. We found that mBSA challenge in the femur-tibial joint of immunized mice induced a dose- and time-dependent mechanical hypernociception. The local IL-17 concentration within the mBSA-injected joints increased significantly over time. Moreover, co-treatment of mBSA challenged mice with an antibody against IL-17 inhibited hypernociception and neutrophil recruitment. In agreement, intraarticular injection of IL-17 induced hypernociception and neutrophil migration, which were reduced by the pre-treatment with fucoidin, a leukocyte adhesion inhibitor. The hypernociceptive effect of IL-17 was also reduced in TNFR1(-/-) mice and by pre-treatment with infliximab (anti-TNF antibody), a CXCR1/2 antagonist or by an IL-1 receptor antagonist. Consistent with these findings, we found that IL-17 injection into joints increased the production of TNF-alpha, IL-1beta and CXCL1/KC. Treatment with doxycycline (non-specific MMPs inhibitor), bosentan (ET(A)/ET(B) antagonist), indomethacin (COX inhibitor) or guanethidine (sympathetic blocker) inhibited IL-17-induced hypernociception. IL-17 injection also increased PGE(2) production, MMP-9 activity and COX-2, MMP-9 and PPET-1 mRNA expression in synovial membrane. These results suggest that IL-17 is a novel pro-nociceptive cytokine in mBSA-induced arthritis, whose effect depends on both neutrophil migration and various pro-inflammatory mediators, as TNF-alpha, IL-1beta, CXCR1/2 chemokines ligands, MMPs, endothelins, prostaglandins and sympathetic amines. Therefore, it is reasonable to propose IL-17 targeting therapies to control this important RA symptom.